Application of a zero-dimensional model to assess the effect of swirl on indicated efficiency. (October 2019) - Broatch, Alberto; Martín, Jaime; García, Antonio; Blanco-Cavero, Diego; Warey, Alok; Domenech, Vicent
Increasing internal combustion engine efficiency continues being one of the main goals of engine research. To achieve this objective, different engine strategies are being developed continuously. However, the assessment of these techniques is not straightforward due to their influence on various intermediate phenomena inherent to the combustion process, which finally result in indicated efficiency trade-offs. During this work, a new methodology to assess these intermediate imperfections on gross indicated efficiency using a zero-dimensional model is developed. This methodology is applied to a swirl parametric study, where it has been concluded that the heat transfer and the rate of heat release are the single relevant changing phenomena. Results show that heat transfer always increases with swirl affecting negatively gross indicated efficiency (around −0.5%), while the impact of combustion velocity is not monotonous. It is enhanced up to a certain swirl ratio (it changes with engine speed) at low engine speed (resulting in an increment of +1.7% in gross indicated efficiency), but it is slowed down at high engine speed with the consequent worsening of gross indicated efficiency (−0.8%).